(untitled) (Bangladesh Journal of Zoology, 2019)
This study was conducted to compare mollusc diversity in migratory bird visiting and non-visiting lakes of Jahangirnagar University campus, Savar, Bangladesh from July, 2016 to June, 2017. A total of 13 species belonging to 6 families under 2 classes of Mollusca were encountered. The class Gastropoda dominated the faunal composition (91%) with 11 species under 5 families and the class Bivalvia constituting (9%) with 2 species under single family. Among them Bellamya bengalensis, Lymnaea accuminata, Indoplnorbis exeutus, Gyraulus convexiusculus, Melanoides tuberculata and Lamellidens marginalis were the most dominating taxa. The highest number of molluscan taxa was from the family Viviparidae (3 spp.) 29% followed by Planorbidae (2 spp.) 27%, Lymnaedae (3 spp.) 23%, Unionidae (2 spp.) 9%, Thiaridae (1 sp.) 8% and lowest from Piladae (2 spp.) 4%. Seasonal variation showed maximum density in the summer and minimum in the monsoon. Correlation (p> 0.05) indicate that B. bengalensis, L. accuminata, I. exustus, L. marginalis had close dependency to soil pH, soil organic Carbon, Soil organic matter and sand particle whereas M. tuberculata and G. convexiusculus show significant positive correlation with silt and clay particle. Biodiversity indices indicating low species diversity and richness of molluscs in both migratory bird visiting and non-visiting lakes. These findings emphasized the importance of protection and management of molluscs fauna in the lakes for supporting the food for the migratory birds. Bangladesh J. Zool. 47(2): 355-366, 2019